Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1128/aac.37.6.1297
|View full text |Cite
|
Sign up to set email alerts
|

A novel dihydrofolate reductase cassette inserted in an integron borne on a Tn21-like element

Abstract: In this study, a 498-bp dhfrXII gene coding for trimethoprim resistance was found inserted in a cassette-like manner in the recombinationally active locus, the integron, borne on a transposon Tn21-like element. The dhfrXII cassette is distinct from those cassettes earlier observed in integrons and was found here upstream (10,21,31,32,51

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 64 publications
(100 reference statements)
3
33
0
2
Order By: Relevance
“…Most (61%) of the class 1 integrons found in this study carried dfr12, orfF and aadA2 cassettes. This pattern was also reported in a urinary E. coli isolate from Turku, Finland [21], and in Shigella strains isolated in Finland, but originating from Asia [21]. The present study also revealed an integron carrying two newly characterised gene cassettes, dfr17 and aadA4.…”
Section: Discussionsupporting
confidence: 56%
“…Most (61%) of the class 1 integrons found in this study carried dfr12, orfF and aadA2 cassettes. This pattern was also reported in a urinary E. coli isolate from Turku, Finland [21], and in Shigella strains isolated in Finland, but originating from Asia [21]. The present study also revealed an integron carrying two newly characterised gene cassettes, dfr17 and aadA4.…”
Section: Discussionsupporting
confidence: 56%
“…The dfrA12 gene encodes a variant of the dihydrofolate reductase gene and the aadA2 gene confers resistance to streptomycin. The dfrA12 gene product confers a 10-times higher level of resistance to trimethoprim than the most common trimethoprim resistance gene dfraA1 (Heikkila et al, 1993). The dfrA12-orf-aadA2 gene cluster has previously been seen in several strains, including an E. coli O157 isolate (GenBank accession no.…”
Section: S Enteritidis Integronsmentioning
confidence: 99%
“…AF335108, unpublished), a Serratia marcescens isolate (GenBank accession no. AF284063, unpublished), a Spanish S. Typhimurium phage type U302 isolate (Guerra et al, 2001;Echeita et al, 2001), an E. coli Shiga-toxin producing O111 : H8 isolate from the USA (Zhao et al, 2001), E. coli isolates from Taiwan (Chang et al, 2000b), E. coli and Shigella isolates from Finland (Heikkila et al, 1993), an epidemic Vibrio cholerae O1 strain from Guinea-Bissau (Dalsgaard et al, 2000) and in an S. Typhimurium DT104a isolate originating from Australia (this report).…”
Section: S Enteritidis Integronsmentioning
confidence: 99%
“…The number of different sized restriction fragments that showed this combination of these two genes suggest that the integrase may be incorporated into a number of different Tn21 like elements such as Tn8O56 [15] which may insert at random sites into the chromosome. It is unclear why the integrase gene of Tn2l which is normally associated with DHFR genes on plasmids [13,15,26,31] should show a preference for integration into the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty of these isolates (82%) had Tn7 located in the attTn7 site. The type II, V, VII and XII DHFRs have all been found as cassette structures on self transmissible plasmids in the integron of Tn2l like elements [13,31]. The following other DHFRs have been observed to contain the characteristic repeats that suggest that the gene forms part of a cassette: VI [15] and the type lb of Tn 4132 [32].…”
Section: Introductionmentioning
confidence: 98%